Accountability, transparency, and fraud propensity in village governments: The mediating role of justice - Putra, Veri Anang; Putra, Wahyu Manuhara (Journal of Accounting and Investment, 2025)
Research aims: This study aims to examine the influence of accountability and transparency on fraud propensity in village governments.Design/Methodology/Approach: This research uses a quantitative survey with a sample of 343 village officials from 64 villages in Indonesia using purposive sampling method. Hypothesis testing in this study uses Structural Equation Modeling-Partial Least Squares (SEM-PLS).Research findings: The results of the study indicate that accountability and transparency do not have an effect on the propensity for fraud in village governments. This finding differs from the direct effect results, which show that accountability and transparency do influence justice. Meanwhile, the mediation analysis through the justice variable also shows an insignificant effect.Theoretical contribution/ Originality: This research makes an original contribution by incorporating the concept of justice in the analysis of the relationship between accountability, transparency, and fraud propensity in village governments, extending the literature that has previously focused more on the corporate sector or central government. It also offers a new perspective on how justice strengthens fraud prevention at the village government level.Research limitation/Implication: The theoretical approach used is relevant but not enough to capture all the dynamics that occur in the field related to budget management and government supervision and the use of questionnaires with Social desirability research instruments.